Nasikh-mansukh; pengertian, pro kontra Eksistensi, bentuk-bentuk dalam al-qur’an, dan hikmahnya - NAVISAH, DEWI (Maliki Interdisciplinary Journal, 2024)
This article discusses the concept of Nasikh wa Mansukh in Islamic Sharia law, covering definitions, conditions, types, and classifications of abrogation in the Qur’an and Sunnah. Etymologically, naskh means to remove or transfer something from one place to another. In Sharia terminology, naskh refers to the abrogation of Sharia law through a divine legislative address (khitab syar’i). The article highlights the distinction between the abrogated law (mansukh) and the abrogating law (nasikh). Examples of abrogation in the Qur’an, such as the change in the direction of prayer (qibla), and instances where laws are abrogated without removing the textual verse, are explored. The discussion includes the conditions for valid abrogation and scholars’ perspectives on the different types of abrogation, such as the abrogation of the Qur’an by the Sunnah and vice versa. The existence of nasikh wa mansukh among various Islamic schools of thought is analyzed to show the diversity of understanding within the Muslim community. This article aims to provide a comprehensive understanding of the role of nasikh wa mansukh in the development of Sharia law and its implications for the study of the Qur’an and Sunnah.